The Mechanism of Short-Term Monocular Pattern Deprivation-Induced Perceptual Eye Dominance Plasticity - Tao, Jiayu; Yang, Zhijie; Li, Jinwei; Cheng, Zhenhui; Li, Jing; Huang, Jinfeng; Wu, Di; Zhang, Pan (Frontiers in Human Neuroscience, 2022)
Previously published studies have reported that 150 minutes of short-term monocular deprivation temporarily changes perceptual eye dominance. However, the possible mechanisms underlying monocular deprivation-induced perceptual eye dominance plasticity remain unclear. Using a binocular phase and contrast co-measurement task and a multi-pathway contrast-gain control model (MCM), we studied the effect of 150 minutes of monocular pattern deprivation (MPD) in normal adult subjects. The perceived phase and contrast varied significantly with the interocular contrast ratio, and after MPD, the patched eye (PE) became dominant. Most importantly, we focused on the potential mechanisms of the deprivation effect. The data of an averaged subject was best fitted by a model, which assumed a monocular signal enhancement of the PE after the MPD. The present findings might have important implications for investigations of binocular vision in both normal and amblyopic populations.